Frequency of Effector Memory Cells Expressing Integrin α4β7 Is Associated With TGF-β1 Levels in Therapy Naïve HIV Infected Women With Low CD4+ T Cell Count - Kasarpalkar, Nandini J.; Bhowmick, Shilpa; Patel, Vainav; Savardekar, Lalita; Agrawal, Sachee; Shastri, Jayanthi; Bhor, Vikrant M. (Frontiers in Immunology, 2021)
Integrin α4β7 expressing CD4+ T cells are preferred targets for HIV infection and are thought to be predictors of disease progression. Concurrent analysis of integrin α4β7 expressing innate and adaptive immune cells was carried out to in antiretroviral (ART) therapy naïve HIV infected women in view of their contribution to HIV induced immune dysfunction. Our results demonstrate a HIV infection associated decrease in the frequency of integrin α4β7 expressing endocervical T cells along with an increase in the frequency of integrin α4β7 expressing peripheral monocytes and central memory CD4+ T cells, which are considered to be viral reservoirs. We report for the first time an increase in levels of soluble MAdCAM-1 (sMAdCAM-1) in HIV infected individuals as well as an increased frequency and count of integrin β7Hi CD8+ memory T cells. Correlation analysis indicates that the frequency of effector memory CD8+ T cells expressing integrin α4β7 is associated with levels of both sMAdCAM-1 and TGF-β1. The results of this study also suggest HIV induced alterations in T cell homeostasis to be on account of disparate actions of sMAdCAM-1 and TGF-β1 on integrin α4β7 expressing T cells. The immune correlates identified in this study warrant further investigation to determine their utility in monitoring disease progression.